2014
DOI: 10.1159/000358287
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Small-Bowel Mucosal Injury between Low-Dose Aspirin and Non-Aspirin Non-Steroidal Anti-Inflammatory Drugs: A Capsule Endoscopy Study

Abstract: Background/Aims: The differences in the severity of small-bowel toxicity induced by aspirin and non-aspirin non-steroidal anti-inflammatory drugs (NSAIDs) remain unclear. This study aimed at clarifying these differences in small-bowel mucosal injury by using capsule endoscopy (CE). Methods: We retrospectively compared the records of 78 and 40 obscure gastrointestinal bleeding patients receiving low-dose aspirin (LDA) and non-aspirin NSAIDs, respectively. All patients were found to have small-bowel mucosal inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 76 publications
1
13
1
2
Order By: Relevance
“…The characteristics of small bowel injury seen in chronic LDA users have been reported recently [14,[36][37][38][39][40][41]. Representative endoscopic findings in patients taking LDA are shown in Figs.…”
Section: Characteristics Of Small Bowel Injury Seen In Chronic Lda Userssupporting
confidence: 58%
“…The characteristics of small bowel injury seen in chronic LDA users have been reported recently [14,[36][37][38][39][40][41]. Representative endoscopic findings in patients taking LDA are shown in Figs.…”
Section: Characteristics Of Small Bowel Injury Seen In Chronic Lda Userssupporting
confidence: 58%
“…40 It is important to note that the use of selective or enteric-coated NSAIDs is also responsible for mucosal damage in the small bowel. [41][42][43][44][45][46][47][48][49] For example, Shiotani et al 41 observed large erosions and ulcers in 60% of young healthy volunteers after 7 days of ingestion of 100 mg of entericcoated aspirin.…”
Section: What Are the Potential Long-term Health Consequences Of Drugmentioning
confidence: 99%
“…42 In light of these data, it might be reasonable to assume that mucosal lesions observed in persons not taking NSAIDs were caused by other, as yet, undisclosed factors such as stress, 43 diet and lifestyle (eg, vitamin D deficiency), 44 or infectious agents. 45 Clinical evidence points, however, to several important consequences related to the effects of NSAIDs on the small intestine: (1) occult GI bleeding and microcytic anemia, 15,41,46 (2) worsening of underlying disease (chronic liver and kidney diseases), 17,25,26 (3) diverticulitis and diverticular bleeding, 47 (4) inflammatory bowel disease, 48 and (5) symptoms consistent with dyspepsia and irritable bowel syndrome (IBS). 49,50 However, the effect of NSAID-related damage might be subclinical, resulting only in anti-inflammatory reaction limited to the mucosal surface and increased intestinal permeability, phenomena that are not routinely measured in clinical practice.…”
Section: What Are the Potential Long-term Health Consequences Of Drugmentioning
confidence: 99%
“…Less than 1% of overt or obscure gastrointestinal bleeding cases can be attributed to small bowel ulcerative lesions [10] . Type of NSAID treatment (aspirin, non-aspirin NSAIDs) and patient age can increase the risk for a bleeding episode [11] . The role of a concurrent peptic ulcer is rather unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Small bowel ulcerative lesions were 15% more frequent in our study than in Watanabe et al [12] report, a small study on 11 nonbleeding gastric ulcer patients receiving low-dose aspirin and proton pump inhibitors. The difference could be attributed to the younger age of Watanabe et al [19] patients and the use of low dose aspirin, a less toxic NSAID [11,27] . Inclusion of patients with duodenal ulcer, in our study, could not influence the final outcome, as we found no difference between gastric and duodenal ulcer patients.…”
mentioning
confidence: 99%